Potassium-pillared Na4FeV(PO4)3@C cathode for high-performance sodium-ion batteries - Jiafeng Zhou; Wei Zhang; Jin Bai; Qingqing Wang; Bo Ding; Hao Gong (Electrochemistry Communications)
Due to the open 3D framework structure and relative high capacity, the NASICON type Na3V2(PO4)3 has aroused enormous attention as the cathode material for sodium-ion batteries. However, it still suffers from the toxicity and high cost of vanadium elements, coupled with low electronic conductivity. In this study, we partially substituted V with the environmentally friendly and cost-effective transition element Fe and doped K into the Na site to fabricate a series of Na4-xKxFeV(PO4)3@C composites using a facile sol-gel method. The structural stability, Na+ mobility and electronic conductivity can significant improved by replacing Na+ with K+ and applying a carbon coating. Consequently, the Na3.9K0.1FeV(PO4)3@C electrode delivers a reversible discharge capacity of 83.85 mAh g−1 at 5C after 3000 cycles, with a capacity retention of 91.7 %. It also exhibits an outstanding rate performance with a specific discharge capacity of 83.88 mAh g−1 even at 20.0C. The kinetic analyses and ex-situ characterizations confirm that a small volume change, the pseudocapacitive- dominated sodium storage behavior and highly reversible redox reaction (Fe2+/3+ and V3+/4+) occur during the electrochemical reaction process. Finally, the optimized K-doped NFVP cathode also demonstrates great potential in practical utilization through the evaluation of electrochemical performance for full cells.